Work and occupational profile of Eastern African immigrants in the United States: a historical overview. Issue 3 (27th May 2019) - Woldeab, Daniel; Yawson, Robert; Woldeab, Irina
ABSTRACT: This paper discusses the trends and patterns of emigration from Eastern Africa, otherwise known as the Horn of Africa. In particular, the paper focuses on the countries that collectively account for most African immigrants to the United States (US), namely Eritrea, Ethiopia, Sudan, and Somalia. Using a review of literature, the paper provides some explanation of the history of immigration from East Africa to the US, and an examination and discussion of the root causes, the trends, and patterns resulting in refugees and immigration to the country. An explanation of the causes for this is offered by drawing connections to the work and occupational profiles of these immigrants, once they are in the US, within a historical context. This historical perspective analysis paves the way for more research on immigration and HRD.